2019
DOI: 10.4103/ajns.ajns_234_19
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on the management of brain arteriovenous malformations

Abstract: Brain arteriovenous malformations (bAVMs) are complex, heterogeneous, and uncommon intracranial lesions. They can be treated by one or a combination of the following treatment modalities, namely embolization, radiosurgery, or microsurgical resection. In Spetzler-Martin Grade 4 and 5 arteriovenous malformations (AVMs), conservative management may be the best option. A group of experts in the management of AVMs of different disciplines gathered in January 2019 in Hanoi to compile the "Expert Consensus on the Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 51 publications
(115 reference statements)
2
47
0
Order By: Relevance
“…Just over half the adult recurrences were treated by surgical excision, stereotactic radiosurgery (SRS) was the next most common option. A systematic review in 2018 that included paediatric cases found that surgery (59%) and SRS (37%) were the most common methods of treatment [4] and a recent consensus paper recommended that recurrent lesions be treated surgically [33].…”
Section: Discussionmentioning
confidence: 99%
“…Just over half the adult recurrences were treated by surgical excision, stereotactic radiosurgery (SRS) was the next most common option. A systematic review in 2018 that included paediatric cases found that surgery (59%) and SRS (37%) were the most common methods of treatment [4] and a recent consensus paper recommended that recurrent lesions be treated surgically [33].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the treatment of choice in AVMs. 13,14 Complete resection ensures cure of the lesion. Stereotactic radiosurgery causes progressive occlusion of vessels, but unfortunately the effect occurs in time, and until 1-2 years the nidus is still active.…”
Section: Discussionmentioning
confidence: 99%
“…15 Conservative treatment and stereotactic radiosurgery can be tried in patients with small, unruptured, located in eloquent areas AVMs. 13 Surgical principles are represented by early coagulation of feeding arteries, circumferential dissection of the nidus progressing deep and, after complete arterial disconnection of the nidus occlusion of draining veins. 10 We do not perform preoperative embolization of AVMs because it carries the risk of intraprocedural nidus rupture and developing normal perfusion pressure breakthrough.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial arteriovenous malformations (IAVMs) are congenital, heterogeneous, and rare vascular abnormalities that can cause intracranial hemorrhage, headache, seizure, and death [1]. IAVMs with an abnormal nidus of blood vessels shunt blood from the arterial to the venous system and bypass an intervening capillary bed [2].…”
Section: Introductionmentioning
confidence: 99%